Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(=6x^4-9x^3+3x^2-4x^3+6x^2-2x+10x^2-15x+5\)
\(=6x^4-13x^3+19x^2-17x+5\)
b: \(=6x^4-\dfrac{9}{4}x^3-\dfrac{9}{2}x^2-\dfrac{8}{3}x^3+x^2+2x-\dfrac{20}{3}x^2+\dfrac{5}{2}x+5\)
\(=6x^4-\dfrac{59}{12}x^3-\dfrac{67}{6}x^2+\dfrac{9}{2}x+5\)
c: \(=3x^4-\dfrac{9}{8}x^3-\dfrac{3}{4}x^2+8x^3-3x^2-6x-\dfrac{4}{3}x^2+\dfrac{1}{2}x+1\)
\(=3x^4-\dfrac{55}{8}x^3-\dfrac{25}{12}x^2-\dfrac{11}{2}x+1\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(=\dfrac{1-2x+3+2y+2y-4}{6x^3y}=\dfrac{-2x+4y}{6x^3y}=\dfrac{-2\left(x-2y\right)}{6x^3y}=\dfrac{-x+2y}{3x^3y}\)
b: \(=\dfrac{x^2-2+2-x}{x\left(x-1\right)^2}=\dfrac{x\left(x-1\right)}{x\left(x-1\right)^2}=\dfrac{1}{x-1}\)
c: \(=\dfrac{3x+1+x^6-3x}{x^2-3x+1}\)
\(=\dfrac{x^6+1}{x^2-3x+1}\)
d: \(=\dfrac{x^2+38x+4+3x^2-4x-2}{2x^2+17x+1}\)
\(=\dfrac{4x^2+34x+2}{2x^2+17x+1}=2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\dfrac{x^2-4}{2x^2-4x}\)
\(=\dfrac{\left(x-2\right)\left(x+2\right)}{2x\left(x-2\right)}\)
\(=\dfrac{x+2}{2x}\)
b) \(\dfrac{2x-x^2}{x^2-4x+4}\)
\(=\dfrac{x\left(2-x\right)}{\left(x-2\right)^2}\)
\(=\dfrac{x\left(2-x\right)}{\left(2-x\right)^2}\)
\(=\dfrac{x}{2-x}\)
c) \(\dfrac{x^2-xy-x+y}{x^2+xy-x-y}\)
\(=\dfrac{x\left(x-y\right)-\left(x-y\right)}{x\left(x+y\right)-\left(x+y\right)}\)
\(=\dfrac{\left(x-y\right)\left(x-1\right)}{\left(x+y\right)\left(x-1\right)}\)
\(=\dfrac{x-y}{x+y}\)
d) \(\dfrac{5x^2+10x+5}{x+x^2}\)
\(\dfrac{5\left(x^2+2x+1\right)}{x\left(1+x\right)}\)
\(=\dfrac{5\left(x+1\right)^2}{x\left(x+1\right)}\)
\(=\dfrac{5\left(x+1\right)}{x}\)
e) \(\dfrac{3x^2+3x}{\left(x+1\right)\left(2x+6\right)}\)
\(=\dfrac{3x\left(x+1\right)}{\left(x+1\right).2\left(x+3\right)}\)
\(=\dfrac{3x}{2\left(x+3\right)}\)
f) \(\dfrac{\left(2-3x\right)\left(x+1\right)}{x^2+2x+1}\)
\(=\dfrac{\left(2-3x\right)\left(x+1\right)}{\left(x+1\right)^2}\)
\(=\dfrac{2-3x}{x+1}\)
\(C=\dfrac{1}{x+2}+\dfrac{1}{\left(x+2\right)\left(4x+7\right)}\\ C=\dfrac{4x+7}{\left(x+2\right)\left(\left(4x+7\right)\right)}+\dfrac{1}{\left(x+2\right)\left(4x+7\right)}\\ C=\dfrac{4x+7+1}{\left(x+2\right)\left(4x+7\right)}\\ C=\dfrac{4x+8}{\left(x+2\right)\left(4x+7\right)}\\ C=\dfrac{4\left(x+2\right)}{\left(x+2\right)\left(4x+7\right)}\\ C=\dfrac{4}{4x+7}\)
\(D=\dfrac{1-3x}{2x}+\dfrac{3x-2}{2x-1}+\dfrac{3x-2}{2x-4x^2}\\ D=\dfrac{1-3x}{2x}+\dfrac{3x-2}{2x-1}-\dfrac{3x-2}{4x^2-2x}\\ D=\dfrac{\left(1-3x\right)\left(2x-1\right)}{2x\left(2x-1\right)}+\dfrac{\left(3x-2\right)2x}{\left(2x-1\right)2x}-\dfrac{3x-2}{2x\left(2x-1\right)}\\ C=\dfrac{\left(1-3x\right)\left(2x-1\right)+\left(3x-2\right)2x-\left(3x-2\right)}{2x\left(2x-1\right)}\\ C=\dfrac{\left(1-3x\right)\left(2x-1\right)+\left[\left(3x-2\right)2x-\left(3x-2\right)\right]}{2x\left(2x-1\right)}\\ C=\dfrac{\left(1-3x\right)\left(2x-1\right)+\left(3x-2\right)\left(2x-1\right)}{2x\left(2x-1\right)}\\ C=\dfrac{\left[\left(1-3x\right)+\left(3x-2\right)\right]\left(2x-1\right)}{2x\left(2x-1\right)}\\ C=\dfrac{-\left(2x-1\right)}{2x\left(2x-1\right)}\\ C=-\dfrac{1}{2x}\)
bn lm có viết nhầm k đấy